2019
DOI: 10.1039/c9dt03183a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and biological studies of multidentate gold(i) and gold(iii) NHC complexes

Abstract: The synthesis and characterization of a novel macrocyclic Au(iii) N-heterocyclic carbene (NHC) complex, a novel macrocyclic tetra-NHC benzimidazole ligand, and the corresponding Ag(i) and Au(i) complexes and initial biological studies are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…At the beginning of the twenty-first century, gold(III) porphyrin complex, with satisfying physiological stability, was reported like promising anticancer agent with IC 50 values in the range of 0.73-0.11 µM. The studies against normal and cisplatin-resistant ovarian cancer have shown the ability of gold(III) porphyrin complex, in vitro and in vivo, to exceed cisplatin resistance without affecting health tissue (Lum et al, 2014;Bauer et al, 2019). Furthermore, carbamate-based Au(III) complexes were used for animal experiments and based on the observed data of clinical studies gave promising results of good anticancer effects (Marzano et al, 2011;Gu et al, 2019).…”
Section: Cytotoxic Activity Of Gold(iii) Complexesmentioning
confidence: 99%
“…At the beginning of the twenty-first century, gold(III) porphyrin complex, with satisfying physiological stability, was reported like promising anticancer agent with IC 50 values in the range of 0.73-0.11 µM. The studies against normal and cisplatin-resistant ovarian cancer have shown the ability of gold(III) porphyrin complex, in vitro and in vivo, to exceed cisplatin resistance without affecting health tissue (Lum et al, 2014;Bauer et al, 2019). Furthermore, carbamate-based Au(III) complexes were used for animal experiments and based on the observed data of clinical studies gave promising results of good anticancer effects (Marzano et al, 2011;Gu et al, 2019).…”
Section: Cytotoxic Activity Of Gold(iii) Complexesmentioning
confidence: 99%
“…In addition to the tetradentate porphyrin ligands, stabilization of the gold(III) ion can also be achieved by coordination with the tridentate (C ∧ N ∧ C, C ∧ N ∧ N or N ∧ C ∧ N) pincer ligand containing deprotonated C-donor atom(s) (C − ) and/or neutral σ-donating N-heterocyclic carbene (NHC) ligand(s), affording gold(III) complexes with high physiological stability and promising anticancer properties (Bertrand et al, 2017 ; Carboni et al, 2018 ; Bauer et al, 2019 ; Fares et al, 2020 ; Guarra et al, 2020 ). In this context, we have described the antitumor-active [Au III (C ∧ N ∧ C)(NHC)] + (H 2 C ∧ N ∧ C = 2,6-diphenylpyridine) complexes ( 5 and 6 ).…”
Section: Anticancer Cyclometalated Gold(iii) N-heterocyclic Carbene Cmentioning
confidence: 99%
“…The performances of the dinuclear complexes, in terms of both activity and selectivity, were compared to their corresponding mononuclear counterparts and to dinuclear complexes not having carbohydrate-functionalized NHCs. Dinuclear Au(I) complexes with one or two bridging diNHC carbene ligands were reported to present anticancer properties, acting by inhibiting the thioredoxin reductase TrxR or by leading to mitochondria-induced apoptosis [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%